Portrait of Poverty and Education in Pandeglang Regency: Challenges for the Golden Generation 2045 - Nurlia, Elly; Mahpudin, Mahpudin; Lokman, Asmidar; Wawan, Wawan (Journal of Governance, 2024)
This research aims to observe the phenomenon of poverty that reflects the inequality of women's education in Muruy Village, Menes Sub-district, Pandeglang Regency. The main focuses of the research are illiterate women who are often neglected by government policies and experience negative stigma in the community. As mothers, their role is crucial in their children's education, considering that mothers are the first educational institution for their children. The inability to read and write among mothers in Muruy Village certainly hampers this role, raising questions about the preparation of the 2045 golden generation expected by the government. Through a phenomenological approach and social justice theory, this research will collect in-depth data, descriptions, and mapping of the condition of illiterate women in the area. The results of the research are expected to be an effective policy recommendation for the Pandeglang Regency Government to address social injustice in education and break the cycle of poverty to realize the golden generation 2045. The results of the research demonstrate that the economic inequality that manifests in the poverty of Muruy villagers is correlated with the lack of education. The illiteracy phenomenon that occurs among many women in Muruy Village puts them in a dilemma. The reason is that in the productive role, illiterate women have no room to help the family finances because of their minimal skills. Meanwhile, in the reproductive role, they also have trouble providing proper education and parenting to their children. This condition results in an obvious role dilemma for illiterate women that affects their next generation. However, there is positive expectation from this phenomenon; among illiterate women, almost all of them have realized that education is an important aspect for their children.